2015
DOI: 10.3892/etm.2015.2644
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular polymeric substance from Aphanizomenon flos-aquae induces apoptosis via the mitochondrial pathway in A431 human epidermoid carcinoma cells

Abstract: Abstract. Extracellular polymeric substance (EPS) is a substance secreted during algal growth, which has been found to have numerous health-promoting effects. In the present study, A431 human epidermoid carcinoma cells were selected as target cells and cultivated in vitro as an experimental model to investigate the anti-cancer effect of extracellular polymeric substances from Aphanizomenon flos-aquae (EPS-A) and the possible underlying mechanism. Apoptosis-and cell cycle-associated molecules as well as the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Initially, the research on cyanobacterial EPS was mainly focused on the potential of these polymers as bioremediation agents for the treatment of industrial and domestic wastewaters, namely for the removal of ammonia, phosphates, and heavy metals [17,18,19,20,46,47,48]. However, as knowledge accumulated, their putative antiviral, antimicrobial, antioxidant, anticoagulant, immunomodulatory, and antitumor activities started to be unveiled [26,29,30,32,33,34,49,50,51,52,53,54,55,56,57,58], opening the way for the use of cyanobacterial EPS in biomedical applications.…”
Section: Cyanobacterial Extracellular Polymeric Substances (Eps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the research on cyanobacterial EPS was mainly focused on the potential of these polymers as bioremediation agents for the treatment of industrial and domestic wastewaters, namely for the removal of ammonia, phosphates, and heavy metals [17,18,19,20,46,47,48]. However, as knowledge accumulated, their putative antiviral, antimicrobial, antioxidant, anticoagulant, immunomodulatory, and antitumor activities started to be unveiled [26,29,30,32,33,34,49,50,51,52,53,54,55,56,57,58], opening the way for the use of cyanobacterial EPS in biomedical applications.…”
Section: Cyanobacterial Extracellular Polymeric Substances (Eps)mentioning
confidence: 99%
“…The mechanism of selective cytotoxicity displayed by different EPS with antitumor properties is also being evaluated. Studies performed with EPS isolated from Aphanothece halophytica , Nostoc sphaeroides , Aphanizomenon flosaquae , and Synechocystis ∆ sigF revealed that the antitumor effect of these polymers is due to the induction of apoptosis in the tumor cells [27,34,57,58].…”
Section: Cyanobacterial Extracellular Polymeric Substances (Eps)mentioning
confidence: 99%
“…AFA is a filamentous and heterocytic cyanobacterium, commonly found in nutrient-rich freshwaters as one of the dominant species in cyanobacterial bloom [20]. AFA is also called “Klamath algae”, due to its notably growth in the Upper Klamath Lake in Oregon State, USA, and the no longer used term “blue-green algae”, associated to the Cyanobacteria phylum.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent in vitro studies on extracellular polymeric substances from AFA (EPS‐A) expand on alternative apoptotic pathways. EPS‐A has been shown to induce cell cycle arrest and apoptosis via loss of mitochondrial function in A431 epidermoid carcinoma cells . This, in conjunction with cytokine activity, may result in loss of epidermal cell‐to‐cell adhesion and antibody production seen in PF.…”
mentioning
confidence: 99%